Webinar Series: Higiene Sanitasi Dalam Sistem Manajemen Keamanan Pangan - setyawati, nur falah; Mappangile , Andi Surayya (EUNOIA, 2022)
The socialization activity regarding hygiene sanitation in the food safety management system is a community service activity. The purpose of this activity is an effort to help people maintain the safety of food consumed and processed during the Covid-19 pandemic. Activities are carried out through a webinar series program to increase public knowledge about hygiene sanitation requirements and procedures for managing food and beverages that meet health standards. The community service method was in the form of talk shows and discussion activities which were attended by participants, namely IPEMI members, alumni and students of the D4K3 Uniba vocational faculty. The results showed a positive response and high active participation of participants.